2018
DOI: 10.1002/micr.30341
|View full text |Cite
|
Sign up to set email alerts
|

A literature review and meta‐analysis of outcomes in microsurgical reconstruction using vasopressors

Abstract: Our results suggest that vasopressor utilization does not directly result in increased complications. Flaps that received vasopressors had a statistically lower rate of take-back and failure. Due to the paucity of data available for analysis and limited reporting relating flap characteristics to outcomes, prospective, well-designed studies are necessary to verify the safety of vasopressor use in microsurgical reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…27,28 Our series differs from existing literature, where phenylephrine or ephedrine dominates. 8,23 Only one previous study includ-ed the administration of metaraminol, and this was in the minority. 15 Metaraminol was by far the most commonly administered agent in our series, so it is likely to be an indicator rather than a cause of poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Our series differs from existing literature, where phenylephrine or ephedrine dominates. 8,23 Only one previous study includ-ed the administration of metaraminol, and this was in the minority. 15 Metaraminol was by far the most commonly administered agent in our series, so it is likely to be an indicator rather than a cause of poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Largely different end points, ranging from 5 days to 3 months, alongside inconsistent outcomes, defined from total flap loss to flap complications requiring surgical revision, naturally make comparison difficult. 8 Second, while many studies have investigated the impact of vasopressor use on flap outcomes, none have addressed the effect of different methods of administration (i.e., continuous IV administration or repeated boluses). These methodological difficulties indicate that further clear quantitative data are required.…”
mentioning
confidence: 99%
“…The safety of vasoactive agents in reconstructive microsurgery observed in this study falls in line with the findings of several recent publications. 9 , 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…The variability of the types of free flaps utilized in this study enhances its generalizability to the field of head and neck free flap reconstruction as a whole. Overall these results are consistent with multiple other clinical studies examining pressors in head and neck reconstruction (Chao, Taylor, Rahmati, & Rohde, 2014; Harris et al, 2012; Kelly et al, 2014; Monroe et al, 2010; Monroe et al, 2011), as well as larger studies evaluating the effect of vasopressors in free flap reconstruction of the breast, head and neck, extremities, and trunk (Table 4; Chan, Chow, & Liu, 2013; Chen et al, 2010; Fang et al, 2018; Knackstedt, Gatherwright, & Gurunluoglu, 2019; Nelson et al, 2017). The study by Nelson et al (2017) observed retrospectively that within 682 patients undergoing 1,039 flaps for breast reconstruction there was no increase in intraoperative thrombotic events (arterial or venous) or flap loss associated with vasopressor administration, but they did have a higher rate of minor complications (wound healing issues, seroma, infection, partial flap loss, and fat necrosis): 53% in the vasopressor group and 43% in those who did not receive vasopressors.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular note, phenylephrine was the pressor used during the microvascular anastomosis of the case of the flap failure that occurred in the pressor group. As the meta‐analysis by Knackstedt et al (2019) describes, many surgeons recommend against phenylephrine use during microsurgical reconstruction if a vasopressor is required. Similarly, Retrouvey et al (2020) observed a trend toward increased odds of digit failure in patients who had received phenylephrine intraoperatively during their digit reimplantation/revascularization.…”
Section: Discussionmentioning
confidence: 99%